If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -5 + x = 5 + 4 + -2 Combine like terms: 11 + -5 = 6 6 + x = 5 + 4 + -2 Combine like terms: 5 + 4 = 9 6 + x = 9 + -2 Combine like terms: 9 + -2 = 7 6 + x = 7 Solving 6 + x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = 7 + -6 Combine like terms: 6 + -6 = 0 0 + x = 7 + -6 x = 7 + -6 Combine like terms: 7 + -6 = 1 x = 1 Simplifying x = 1
| 43s^2+14s=0 | | 2y=3y-8 | | -3+13=15x-4-14x | | 44+(7x-3)=90 | | 4acz-4bcz+3ay-3by=0 | | 7y-13y=-18-24 | | 3w-7=28 | | 5b/=27.5 | | 27=z/.3 | | 3/4d=41/2 | | P(x)=5x^4-5x^3-45x^2+45x | | ×/4=20 | | 2/3r=5 | | (3a-2b)+(3a+2b)=0 | | 9h-12=6h-18 | | 24+2x=3x+12 | | .05x+.25y=30 | | 4x+12=28-6x | | x^2-2x-46=2 | | 14.2y=2.84 | | 5(x+1)=6(x+2) | | 2x-7y=-31 | | 32s^4-8s^2=0 | | 1.2b=2.4 | | w-8=5(w+4) | | 4×7×2÷1/2 | | 30x+55y=200 | | 2(x-3)=3(x-3) | | X^2-42x+49=0 | | (2t+3r)(2t-3r)= | | 5x-13=4x+12 | | -b-3=3b |